Determination of Uranium Concentration in child teeth by track detector CR-39 in same middle and south regions of Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
The study of determing Uranium concentration in samples of teeth is the first of its kind in the Iraq . In this study Uranium concentration has been measured was (32) samples of child teeth distributed on the some of middle and south governorate of Iraq (Muthana – Dekar – Basrah – Najaf – Karbalah – Waset – Babel – Baghdad) . The Uranium concentration in teeth samples has been measured by using fission tracks registration in (CR-39) track detector that caused by the bombardment of (U235) with thermal neutrons falx from (24Am.Be) neutron source that has flux of (5x103n.cm-2S-1). The result obtained show that the Uranium concentrations in governorates were (0.18ppm), (0.172ppm), (0.160ppm), 0.150ppm) (0.89ppm), (0.07ppm) , (0.052ppm), (0.020ppm) (0.089ppm), (0.07ppm) , (0.052ppm) , (0.020ppm) (0.089ppm), (0.07ppm) , (0.052ppm) , (0.20ppm) respectively . As a conclusion from the study of Uranium concentration in Muthana governorate that found to be higher than Dekar and Basrah , Najaf , Karbalah, Waset , Babel and Baghdad . These result are higher thin the Uranium concentrations in one studies in Barazil – Bahia state its (0.016ppm) , and in another study in British about (0.018-0.079ppm).